On D. Ya. Petrina’s works in contemporary mathematical physics - Gerasimenko, V. I.; Malyshev, P. V.; Rebenko, A. L. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
This is a brief survey of the works of Prof. D. Ya. Petrina in various branches of contemporary mathematical physics.